On the influence of pore connectivity on performance of membrane filters. (3rd September 2020) - Gu, B.; Renaud, D. L.; Sanaei, P.; Kondic, L.; Cummings, L. J.
Abstract: Abstract : We study the influence of a membrane filter's internal pore structure on its flow and adsorptive fouling behaviour. Membrane performance is measured via (1) comparison between volumetric flow rate and throughput during filtration and (2) control of concentration of foulants at membrane pore outlets. Taking both measures into account, we address the merits and drawbacks of selected membrane pore structures. We first model layered planar membrane structures with intra-layer pore connections, and present comparisons between non-connected and connected structures. Our model predicts that membrane filters with connected pore structures lead to higher total volumetric throughput than those with non-connected structures, over the filter lifetime. We also provide a sufficient criterion for the concentration of particles escaping the filter to achieve a maximum in time (indicative of a membrane filter whose particle retention capability can deteriorate). Additionally, we find that the influence of intra-layer heterogeneity in pore-size distribution on filter performance depends on the connectivity properties of the pores.